Environmental and Sustainability Education Research, Past and Future: Three Perspectives From Late, Mid, and Early Career Researchers. (29th January 2016) - Stevenson, Robert (Bob); Ferreira, Jo-Anne; Emery, Sherridan
Abstract: The first research symposium, organised in conjunction with the Australian Association for Environmental Education (AAEE) biennial conference, began with a dialogue between scholars at three different academic career stages. As we all entered the field at different periods in its development, the first part of our presentation and this article provide our perspectives on the context, approaches and issues that characterised the field at the time we became involved in environmental education (EE) and EE research. The second part of this article presents the lessons we have learnt from EE research, and where we see the field headed in the future.